Building and Applying a Performance Evaluation Scale for the Administrative Bodies of Premier League Football Clubs from the Perspective of Their Management - Imad Saadallah Khamees; Ibrahim Khalil Ibrahim (Indonesian Journal Publisher, 2026)
This research aims to highlight the importance of the administrative aspect in developing sports performance. Athletic achievement is no longer dependent solely on physical and technical factors; administrative performance has become a fundamental element in building teams and champions. Studies have shown that scientific sports management represents the first step in discovering and preparing talents for high-level competition. Here, the role of testing and measurement science emerges as a key tool in evaluation and selection, contributing to the design of sports programs and plans and correcting both administrative and technical pathways. The research problem lies in the need to construct a scientific scale to evaluate the performance of administrative bodies in premier league football clubs, from the perspective of the technical staff who are most closely engaged with these bodies. The research objectives are: (1) to build a scale for evaluating administrative performance, and (2) to apply this scale to a sample of technical staff members in premier league clubs. The study also defines its human, spatial, and temporal domains, specifying the period from January 25, 2026, to February 29, 2026. The significance of the research is in identifying the level of performance of administrative bodies in premier league clubs, revealing strengths and weaknesses, and supporting the development of administrative work to achieve better athletic outcomes